DFT study on the dissolution mechanisms of α-cyclodextrin and chitobiose in ionic liquid. (1st August 2017) - Cao, Bobo; Du, Jiuyao; Cao, Ziping; Sun, Xuejun; Sun, Haitao; Fu, Hui
Graphical abstract: As the potential substitute of fossil fuels, cyclodextrin and chitosan dissolved in [Emim][OAc] were investigated using DFT method, in which non-covalent interactions were identified as the driving force. Both anion and cation in ionic liquid interacting with cyclodextrin and chitosan contributed to the dissolution reaction. AIM, RDG and NBO analyses were employed to characterize the nature of the intermolecular interactions. Highlights: Dissolution mechanism of cyclodextrin and chitosan in [Emim][OAc] is studied. [Emim] + and [OAc] − interacting with carbohydrate contribute to the dissolution. Non-covalent interactions are identified as the driving force of the dissolution. Non-covalent interaction in the dissolution is dominated by hydrogen bonding. Abstract: Density functional theory (DFT) was employed to study the dissolution mechanisms of α-cyclodextrin and chitobiose in 1-ethyl-3-methyl-imidazolium acetate ([Emim][OAc]). Geometrical analysis of the studied complexes indicated that both anion and cation in ionic liquid interacting withα-cyclodextrin and chitobiose contributed to the dissolution reaction. Intermolecular interactions in the complexes were identified as non-covalent interactions, such as hydrogen bonds, van der Waals interactions and repulsions, which were considered as the driving force of dissolution. Among them, hydrogen bonding interactions played a dominant role, which was further visualized in the real space by combination of atoms in molecules (AIM) and reduced density gradient (RDG) techniques. The nature of intermolecular orbital interactions was characterized using natural bond orbital (NBO) theory.